The Letter by Nest-Darejan to her Beloved - Marjory Wardrop,; Venera Urushadze,; Katherine Vivian,; Robert Stevenson, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
div]:bg-bg-000/50 [&_pre>div]:border-0.5 [&_pre>div]:border-border-400 [&_.ignore-pre-bg>div]:bg-transparent [&_.standard-markdown_:is(p,blockquote,h1,h2,h3,h4,h5,h6)]:pl-2 [&_.standard-markdown_:is(p,blockquote,ul,ol,h1,h2,h3,h4,h5,h6)]:pr-8 [&_.progressive-markdown_:is(p,blockquote,h1,h2,h3,h4,h5,h6)]:pl-2 [&_.progressive-markdown_:is(p,blockquote,ul,ol,h1,h2,h3,h4,h5,h6)]:pr-8"> _*]:min-w-0 gap-3 standard-markdown"> The letter by Nestan-Darejan to her beloved is one of the best passages of The Man in the Panther Skin. It reveals hyperbolically irreal, ideal and artistic image of the heroine Nestan, who is depicted as being far from the usual humanly imagination, fighting to save her romantic and sentimental, unlimited love. According to the results of my research, this artistic prototypic image of Nestan served as the basis for the artistic image of Imogen, one of the distinguished heroines of Shakespeare. Features, similar to Nestan, are attributed to Imogen by the English Literary critique. The letter by Nestan reveals one principal thesis of Rustaveli's worldview: on the one hand, the kind and protective God to whom Nestan longs for and the deceitful and ruthless reality, with fatal fate, which Nestan blames for her own and her lover's ill fate, on the other. At the same time, Rustaveli points to one of the primary principles of existence in this world, being a servant to one's own motherland. The letter presents one more philosophical thesis: the only reminder of the person leaving the material world is their presence, in its newly acquired essence, in the memory of the people. The text of The Man in the Panther Skin was published from the edition with variants, published in 1966 (edited by A. Shanidze and A. Baramidze), with the corresponding numbering of stanzas. Text was taken from the translations by Marjory Wardrop, Venera Urushadze, Katherine Vivien and Robert Stevenson as indicated in "Avtandil's Testament" published in the 21st issue of The Kartvelologist. Elguja Khintibidze <fieldset class="flex w-full min-w-0 flex-col"></fieldset>